2019
DOI: 10.1016/j.ijpx.2019.100021
|View full text |Cite
|
Sign up to set email alerts
|

A synbiotic concept containing spore-forming Bacillus strains and a prebiotic fiber blend consistently enhanced metabolic activity by modulation of the gut microbiome in vitro

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 50 publications
2
50
0
Order By: Relevance
“…Duysburgh et al showed that Bacillus spores coadministered with prebiotics in a symbiotic formula, significantly influenced the microbial activity in the intestine, increasing the production of colonic butyrate. This is an important short-chain fatty acid that helps retain the structure of the intestinal barrier and blocks aberrant expression of ZO-1, thus decreasing endotoxemia [30].…”
Section: Discussionmentioning
confidence: 99%
“…Duysburgh et al showed that Bacillus spores coadministered with prebiotics in a symbiotic formula, significantly influenced the microbial activity in the intestine, increasing the production of colonic butyrate. This is an important short-chain fatty acid that helps retain the structure of the intestinal barrier and blocks aberrant expression of ZO-1, thus decreasing endotoxemia [30].…”
Section: Discussionmentioning
confidence: 99%
“…The dietary supplement was able to decrease the amount of acetate and propionate produced and only increased the butyrate production to a certain extent. This result is not common even in in vitro models involving prebiotics and probiotics, where the expected result is an increase of SCFA or no effect at all (60,61) . However, depending on the fermented fibre selected, some in vitro studies can demonstrate a reduction on specifics SCFA (62) , such as the work presented by Yang et al (63) where the propionate amount was decreased after inulin and pectin treatments.…”
Section: Production Of Metabolitesmentioning
confidence: 91%
“…Lactate levels were determined using a commercially available enzymatic assay kit (R-Biopharm, Darmstadt, Germany) according to the manufacturer’s instructions. Ammonium determination was conducted as previously reported by Duysburgh et al [ 55 ].…”
Section: Methodsmentioning
confidence: 99%